Racial disparities in receipt of survivorship care plans among female cancer survivors in Maryland - Jin, Mu; Jones, Miranda R.; Connor, Avonne E. (Frontiers in Cancer Control and Society, 2024)
Background With the increasing number of cancer survivors in the US, survivorship care plans (SCP) have been promoted to improve survivorship outcomes for cancer patients. Few studies have assessed if the receipt of SCPs differs by race/ethnicity. This study evaluated if racial/ethnic disparities exist in SCP receipt among female cancer survivors living in Maryland. Methods Survey data were analyzed for 1,353 non-Hispanic white (NHW) and 280 non-Hispanic Black (NHB) women with a self-reported history of cancer living in Maryland who completed the Maryland Behavioral Risk Factor Surveillance Survey (BRFSS) between 2011 and 2020. Multivariable logistic regression models were used to estimate prevalence odds ratios (PORs) and 95% confidence intervals (CI) for SCP receipt by race/ethnicity. Models were further stratified by demographic, cancer-related, and lifestyle factors to examine effect modification. Results On average, survivors were 66.8 years of age at time of BRFSS survey and 53.5 years of age at time of cancer diagnosis. Compared with NHW survivors, NHB survivors reported higher odds of receiving a summary of cancer treatments (POR = 3.81, 95% CI: 2.27, 6.39), instructions from a doctor for follow-up check-ups (POR = 2.10, 95% CI: 1.00, 4.39), and written or printed instructions (POR = 4.74, 95% CI: 2.12, 10.61). Age at survey (<65 years vs. ≥65 years) (p-interaction term = 0.01) and income level (≤50k vs. >50k) (p-interaction term = 0.04) significantly modified the relationship between race/ethnicity and receiving SCPs. Conclusion Our findings indicate that NHB female cancer survivors in Maryland are more likely to receive SCP information compared to NHW survivors and this association is significantly modified by age at survey and income level. More research is needed at the patient-provider level to gain a better understanding of the impact of SCP delivery to minority cancer populations.